1977
DOI: 10.1083/jcb.73.3.561
|View full text |Cite
|
Sign up to set email alerts
|

Mitogenic activity of pituitary hormones on cell cultures of normal and carcinogen-induced tumor epithelium from rat mammary glands

Abstract: Cell suspensions containing normal or tumor epithelium were readily obtained by enzymatically digesting rat mammary glands from perphenazine-treated (prolactin-hypersecreting) cycling, female virgin animals or hormone-responsive mammary tumors from animals treated with dimethylbenzanthracene. Cell suspensions were fractionated into predominantly epithelial and predominantly stromal cells by their differential rates of attachment to culture dishes. Both normal mammary and tumor epithelial cells were characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
1

Year Published

1979
1979
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(28 citation statements)
references
References 34 publications
2
25
1
Order By: Relevance
“…bFGF was first reported to act as a mitogen for breast cancer cells by Karey and Sirbasku (1988) although it had previously been shown to stimulate the growth of rat mammary myoepithelial and stromal cell lines (Rudland et al, 1977;Smith et al, 1984). In this study, bFGF alone increased cell numbers to a limited extent in the absence of oestradiol but in contrast to the other growth factors tested, bFGF acted synergistically with oestradiol.…”
Section: Discussioncontrasting
confidence: 43%
“…bFGF was first reported to act as a mitogen for breast cancer cells by Karey and Sirbasku (1988) although it had previously been shown to stimulate the growth of rat mammary myoepithelial and stromal cell lines (Rudland et al, 1977;Smith et al, 1984). In this study, bFGF alone increased cell numbers to a limited extent in the absence of oestradiol but in contrast to the other growth factors tested, bFGF acted synergistically with oestradiol.…”
Section: Discussioncontrasting
confidence: 43%
“…The required concentration of an ordinary nutrient is usually on the order of 103 to 1 nmol/mol. Peptide growth factors such as epidermal growth factor, somatomedin, or multiplicationstimulating activity (MSA) are known to stimulate thymidine incorporation into DNA at the order of 10-1 to 10-3 nmol/ml (11)(12)(13)(14). Under our experimental conditions, no significant growth-stimulatory effect of PEtn was observed below 10-1 Cell Biology: Kano-Sueoka et al 5744 Cell Biology: Kano-Sueoka et al nmol/ml.…”
Section: Resultsmentioning
confidence: 68%
“…Although perphenazine treatment (Ben-David, 1968) has been widely used (Salomon et al, 1981;Rudland et al, 1977;Hallowes et al, 1977) to increase the Fig. 5.…”
Section: Discussionmentioning
confidence: 97%
“…Using monolayer systems, Rudland et al (1977) and Hallowes et al (1977) demonstrated that the addition of I + PRL + F, with or without P, to serum-containing media could increase…”
Section: Discussionmentioning
confidence: 98%